1999
DOI: 10.1128/cdli.6.3.330-335.1999
|View full text |Cite
|
Sign up to set email alerts
|

RNAs in the Sera of Persian Gulf War Veterans Have Segments Homologous to Chromosome 22q11.2

Abstract: Reverse transcriptase PCR (RT-PCR) was used for polyribonucleotide assays with sera from deployed Persian Gulf War veterans with the Gulf War Syndrome and a cohort of nonmilitary controls. Sera from veterans contained polyribonucleotides (amplicons) that were obtained by RT-PCR and that ranged in size from 200 to ca. 2,000 bp. Sera from controls did not contain amplicons larger than 450 bp. DNA sequences were derived from two amplicons unique to veterans. These amplicons, which were 414 and 759 nucleotides, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…When only a single military unit is studied, the results cannot be generalized [18,23]. Controls were regularly not included or were inadequate [18,31,32,37,68,77]. Healthy warrior bias can be present if only military personnel on active duty are examined and if veterans rejected as medically un®t are omitted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When only a single military unit is studied, the results cannot be generalized [18,23]. Controls were regularly not included or were inadequate [18,31,32,37,68,77]. Healthy warrior bias can be present if only military personnel on active duty are examined and if veterans rejected as medically un®t are omitted.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, speci®c polyribonucleotides were detected in sera from veterans with Gulf War Syndrome and not in those of nonmilitary controls [77]. It is suggested that exposure to environmental genotoxins during the Gulf War could have led to genetic alterations in a region on chromosome 22q11.2.…”
Section: Exposure To Toxic Agentsmentioning
confidence: 99%
“…More specifically, sequences within short interspersed element DNA, or Alu sequences, are activated by human immunodeficiency virus type 1 (HIV-1) infection (16). Moreover, activation and Alumediated recombination are recognized as contributing factors in the progression of some chronic disorders (27). In addition, with the development of xenogenic therapies for human diseases, there is the potential for nonhuman retroelements to be unintentionally incorporated into the human genome.…”
mentioning
confidence: 99%